Biorefinery of anaerobic digestate in a circular bioeconomy: Opportunities, challenges and perspectives. (September 2022) - Malhotra, Milan; Aboudi, Kaoutar; Pisharody, Lakshmi; Singh, Ayush; Banu, J. Rajesh; Bhatia, Shashi Kant; Varjani, Sunita; Kumar, Sunil; González-Fernández, Cristina; Kumar, Sumant; Singh, Rajesh; Tyagi, Vinay Kumar
Abstract: With the ever-increasing size of anaerobic digesters (AD), the management and disposal of digestate have become a challenging task for AD operators. Anaerobic digestate is rich in nutrients and contaminants; thus, a suitable treatment is required to meet environmental legislation and protect the receiving environment. There has been a thrust among the research efforts in anaerobic digestate management in the last decade. Volarization of digestate into high-value products is necessary to make the AD process more cost-effective. Moreover, digestate utilization helps in recycling the already mined resources. Efforts have been made to use digestate as a feedstock to recover energy and value-added products such as nutrients (N, P), biochar, biofuels, polyhydroxyalkanoates (PHAs), and algal cultivation, which can arguably help to enable the circular economy in modern communities. This communication thoroughly examines the anaerobic digestate-based biorefinery concept and its linkages with the circular bio-economy. This review comprehensively summarized digestate management practices; recovery of renewable fuels and other value-added products from digestate, including bottlenecks and perspectives altogether in digestate management and treatment. The state-of-the-art of commercialization of anaerobic digestate valorization technologies has also been provided. Overall, this review could support decision-makers in identifying environmentally sound and sustainable solutions ahead of time. Graphical abstract: Image 1 Highlights: Critically review of the conventional and emerging digestate management practices. Featured the commercialization of anaerobic digestate valorization technologies. Key challenge & research needs in development of digestate valorization are explored. Various pre-treatment methods can be used to improve the quality of nutrients recovered. Presence of emerging contaminants is a major concern in digestate utilization.